Communication in nursing: a literature review - Carla Monique Lopes Mourão; Anna Paula Sousa da Silva; Mariza Silva de Oliveira; Ana Fátima Carvalho Fernandes (Rev Rene)
This is a descriptive research which aims to analyze knowledge produced on communication in the nursing area from 1996 to 2006, in the Latin-American and Caribbean Literature in Health Sciences (LILACS) database. Among the 98 works collected it was verified that 1997 had the largest publication on the subject, with 16 studies. The source that provided more results was the Latin American Journal with 27 works, followed by dissertations, with 17 works. Regarding the topic of study, it was verified 31 works with “nurse-patient communication” and 16 works with “communication in nursing in the classroom”. We thus concluded that a bigger production of knowledge on communication can effectively contribute to the nursing actions.